Applying Participatory Appraisal of Competitive Advantage (PACA) to Enhance the Competitiveness of the Bakaran Batik Cluster, Pati, Indonesia - Santoso, Joko; Indaryani, Mamik; Handoyo, Ag.Sunarno (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: The batik industry in Indonesia plays a crucial role in preserving cultural heritage and contributing to the national economy. The Bakaran Batik Center in Pati, Central Java, is one of the prominent cultural and economic clusters with a strong local identity. However, increasing competition from modern textile products and new batik producers has challenged its competitiveness in both domestic and international markets. This study aims to analyze competitive advantage strategies using the Participatory Appraisal of Competitive Advantage (PACA) approach at the Bakaran Batik Center. The focus is on identifying internal strengths, market positioning, and collaborative strategies to enhance competitiveness. Materials and methods: The study applied a qualitative descriptive method, conducted at the Bakaran Batik Center, Pati. Data were collected through direct observation, semi-structured interviews, and documentation involving artisans, cooperative leaders, government officials, and consumers. Data validity was ensured through triangulation of sources, techniques, and time. The data analysis process included reduction, presentation, and conclusion drawing to identify the strategic patterns of PACA-based competitive advantage. Results: Findings reveal that Bakaran Batik Center faces strong competition from new entrants offering modern designs and digital marketing strategies. Nevertheless, it maintains competitiveness through authentic hand-drawn batik techniques, continuous motif innovation, product diversification, and cooperative-based business models. Strengthening partnerships with local government, implementing flexible pricing, maintaining product quality, and promoting consumer education have proven effective in building customer loyalty and sustaining long-term competitiveness. Conclusions: The PACA approach effectively enhances the Bakaran Batik Center’s competitiveness by integrating innovation, cultural authenticity, and collaboration. Participatory strategies involving artisans, cooperatives, and local authorities enable Bakaran Batik to preserve its traditional art while adapting to modern market demands, positioning it as a resilient and competitive creative industry.